Studies on some spinel oxides based electrocatalysts for oxygen evolution and capacitive applications. (10th October 2019) - Pal, Shweta; Azad, Uday Pratap; Singh, Ashish Kumar; Kumar, Dinesh; Prakash, Rajiv
Abstract: In the present work the role of oxygen vacancies in improvement of catalytic activity in spinel oxides is reported and further explored for oxygen evolution and capacitive applications. Sol-gel method is used to prepare nickel ferrite (NFO) and for the first time cobalt doped nickel ferrite (CFO and CNFO) spinel oxides for electrocatalytic studies. As prepared NFO. CFO and CNFO are characterized by various spectroscopic and microscopic techniques and the same are used for supercapacitive application as well as for oxygen evolution reaction (OER). The oxygen vacancy is studied by EDAX and XPS analysis and observed that the vacancies are playing crucial role in OER application. Graphical abstract: Image 1